Anti-inflammatory prenylbenzaldehyde derivatives isolated from Eurotium cristatum. (February 2019) - Zhang, Panpan; Jia, Chunxiu; Deng, Yanlian; Chen, Senhua; Chen, Bin; Yan, Sujun; Li, Jing; Liu, Lan
Abstract: Two undescribed prenylbenzaldehyde derivatives, cristaldehydes A and B, and an undescribed quinone derivative, cristaquinone A, along with seven known compounds were isolated from the fungus Eurotium cristatum . The structures of undescribed compounds were determined by spectroscopic analysis including NMR, HR-ESIMS, and single-crystal X-ray diffraction. This is the first report of identification of a dibenzannulated 6, 6-spiroketal derivative, cristaldehyde B, in a natural product. Cytotoxic and anti-inflammatory activities of all compounds were evaluated. Cristaldehyde A and cristaquinone A along with five known compounds showed significant anti-inflammatory activities with IC50 values in the range from 0.37 to 14.50 μ M. Graphical abstract: Two undescribed prenylbenzaldehyde derivatives and one undescribed quinone derivative were isolated from Eurotium cristatum . The cytotoxic and anti-inflammatory activities of all compounds were evaluated. Highlights: Three undescribed compounds were isolated from Eurotium cristatum. This is the first report of a dibenzannulated 6, 6-spiroketal derivative. Eight prenylbenzaldehydes and two quinones exhibited anti-inflammatory activity.